2013
DOI: 10.1007/s00125-013-3106-7
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane docosapentaenoic acid levels are associated with islet autoimmunity: the Diabetes Autoimmunity Study in the Young

Abstract: Aims/hypotheses We previously reported that lower n-3 fatty acid intake and levels in erythrocyte membranes were associated with increased risk of islet autoimmunity (IA) but not progression to type 1 diabetes in children at increased risk for diabetes. We hypothesise that specific n-3 fatty acids and genetic markers contribute synergistically to this increased risk of IA in the Diabetes Autoimmunity Study in the Young (DAISY). Methods DAISY is following 2547 children at increased risk for type 1 diabetes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 51 publications
4
42
2
Order By: Relevance
“…Furthermore, the prospective Diabetes Autoimmunity Study in the Young (DAISY), investigating older children (9 months to 8 years of age), found that high dietary intake and erythrocyte membrane content of n-3 PUFAs were associated with a decreased risk of islet autoimmunity (defined as repeated positivity for at least one autoantibody) [10,11], but not with progression to type 1 diabetes [13]. Results from DAISY as well as the DIPP cohort support the view that early stages of autoimmunity are affected by long-chain n-3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the prospective Diabetes Autoimmunity Study in the Young (DAISY), investigating older children (9 months to 8 years of age), found that high dietary intake and erythrocyte membrane content of n-3 PUFAs were associated with a decreased risk of islet autoimmunity (defined as repeated positivity for at least one autoantibody) [10,11], but not with progression to type 1 diabetes [13]. Results from DAISY as well as the DIPP cohort support the view that early stages of autoimmunity are affected by long-chain n-3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Long-chain n-3 polyunsaturated fatty acid (PUFA) intake and/or status were protectively related to type 1 diabetes-associated autoimmunity or clinical disease in several [9][10][11], but not all [12,13], epidemiological studies. Maternal intake and status of fish-derived fatty acids during pregnancy were not associated with the risk of developing type 1 diabetes in the offspring [9,14,15], with the exception of one case-control study reporting a protective association [16].…”
Section: Methodsmentioning
confidence: 99%
“…A child's serum proportion of dairy-associated fatty acids was related to an increased risk of advanced islet autoimmunity at or closest to the time of seroconversion, whereas that of linoleic acid conferred a lower risk (29). Fatty acid desynthetase (FADS) genes could interact with αlinolenic acid intake, resulting in a protective effect against islet autoimmunity in children with higher number of minor alleles of these genes (66).…”
Section: Childhood Food Consumptionmentioning
confidence: 99%
“…According to these studies, the benefit of n‐3 FA may be in the inhibition of IA seroconversion. More recently, the DAISY Study has shown a reduced risk for IA in children who consume alpha‐linoleic acid rich foods and supplements and have a specific genetic variant in FA desaturation …”
Section: Discussionmentioning
confidence: 99%